Dioecy in Plants – Is It an Important Factor for Phytochemists to Consider? - Simpson, Bradley S. (Planta Medica, 2013)
Plants with separate male and female flowers are termed dioecious. Dioecy is not rare, yet is a characteristic that could potentially impact the phytochemical and subsequent pharmacological properties of a species. This is a brief insight which highlights why the sex of the plant might be an important factor to consider for researchers within phytochemistry related fields.
Keywords: chemistry; dioecy; female; male; medicinal; metabolites; pharmacological; plant